IDENTIFYING BARRIERS TO DATA PROTECTION AND INVESTOR PRIVACY IN EQUITY CROWDFUNDING: EXPERIENCES FROM INDONESIA AND MALAYSIA (UUM Journal of Legal Studies, 2022)
Equity crowdfunding (ECF) in Indonesia is a fundraiser organized to attract many investors to finance social and business activities on online platforms. In Malaysia, ECF reflects small businesses, especially those of entry-level businesses, raising funds from the public through websites registered with the Malaysian Securities Commission. There are differences in legal protection between Indonesia and Malaysia regarding protection of personal data and investor privacy in ECF activities. This study aimed to examine the barriers faced in data protection and privacy related to equity crowdfunding in Indonesia and Malaysia. This normative legal research focused on positive legal norms, laws, and regulations. It is found that Indonesia and Malaysia have different barriers in protecting personal data and investor privacy in ECF activities. In Indonesia, data protection and investor privacy concerning ECF refer to several legal rules for resolving issues regarding personal data. They often encounter conflicting legal rules in the application of personal data protection and investor privacy in ECF activities. Meanwhile, the protection of personal data and investor privacy on ECF activities has been specifically regulated in the Personal Data Protection Act (PDPA) 2010 in Malaysia. Despite the rules regarding the protection of investor data, cases of personal data theft in Malaysia are high as compared to Indonesia. This is due to the lack of legal awareness for the ECF platform organizers in implementing the provisions set out in the PDPA 2010.